Tsunamis observed on and near the Turkish coast - Altinok, Y.; Ersoy, S. (2000)
For centuries, inhabitants of coastal areas have suffered from the effects of tsunamis. Turkey, with a coastline of 8333 km, has experienced many tsunamis. Historical records reveal that, during the observation period over 3000 years, the coastal and surrounding areas of Turkey have been affected by more than ninety tsunamis. These tended to cluster around the Marmara Sea, the city of Istanbul and the gulfs of Izmit, Izmir, Fethiye and Iskenderun. Each of the tsunami occurrences surveyed in this paper deserves further individual study. The most extensive available information concerns the tsunamis associated with the Istanbul Earthquakes of 1509 and 1894, the Eastern Marmara Earthquake in 1963 and that of Izmit in 1999, which disturbed the Marmara Sea; the Earthquake of 1939 in Erzincan in eastern Anatolia; and the 1968 Bartin Earthquake, which affected Fatsa and Amasra on the Black Sea. In addition to these, it is known that a tsunami occurred in 1598 on the shores of the Black Sea in connection with an earthquake at Amasya in northern Anatolia. - Reproduced
Keywords: Earthquakes - Tsunamis; Earthquakes